FAKTOR IDEOLOGI DALAM SIKAP KRITIS POLITIK LUAR NEGERI IRAN TERHADAP BARAT - Ramdhan Muhaimin (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
Iran is one of the countries in the Middle East that has always been oppositional of the United States (US) and Western hegemony in the region. Iran's foreign policy is critical of the US and the West has emerged especially after the revolution in 1979. This critical attitude is compounded by Iran's nuclear technology capabilities. So, in the Middle East, there are two countries with nuclear technology capabilities for both civilian and military purposes: Iran and Israel. While the US called Iran 'the axis of evil' and is a supporter of global terrorism. Iran's relations with Western countries have been always conflictual because of Western distrust. Through an analytical descriptive qualitative method, this research will collect data and information from the library (library research) to analyze constructivism factors as the background of Iran's critical attitude. The constructivism approach in this research is the factor of history and collective identity in the form of the Iranian nation's ideology. From the literature, this research concludes that attitudes in Iran's foreign policy are influenced by the theology of Imamah or itsna asyariah as the ideology of the Iranian people. The ideology of the Shia believes that the establishment of the Republic of Islamic State is a 'stage' to welcome the arrival of Imam Mahdi. Iran's foreign policy aims to maintain this goal. This factor stimulated the revolutionary 1979 so that Iran's conflicting relations with the West.